2018
DOI: 10.1080/17435390.2018.1498929
|View full text |Cite
|
Sign up to set email alerts
|

Differential toxicity of processed and non-processed states of CoCrMo degradation products generated from a hip simulator on neural cells

Abstract: Physico-chemical characteristics of the CoCrMo degradation products have played an important role in cytotoxicity and clinical complications on the orthopedic patients who have metal implants. Previous studies have limited reflection on the physicochemical characteristics of the degradation products generated in vivo, which are very different from individual metal particles and/or ions obtained from different commercial sources. In this study, we aimed to understand the differences in toxicity induced by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 72 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…Wear particles at concentrations in the range of 10–0.1 µg/ml were added to cell cultures for 24 h of incubation. In a previous study by Bijukumar et al we observed that concentrations above 10 µg/ml caused a reduction in cell growth to less than 40% in the case of neuronal cells. Hence, in this experiment, we selected concentrations from 10 to 0.1 μg/ml to evaluate their effect on the cells of interest in this study.…”
Section: Methodsmentioning
confidence: 65%
See 1 more Smart Citation
“…Wear particles at concentrations in the range of 10–0.1 µg/ml were added to cell cultures for 24 h of incubation. In a previous study by Bijukumar et al we observed that concentrations above 10 µg/ml caused a reduction in cell growth to less than 40% in the case of neuronal cells. Hence, in this experiment, we selected concentrations from 10 to 0.1 μg/ml to evaluate their effect on the cells of interest in this study.…”
Section: Methodsmentioning
confidence: 65%
“…(C) Results of the energy‐dispersive X‐ray spectroscopy (EDS) analysis of CoCrMo wear debris to confirm the presence of cobalt and chromium. The results are qualitatively due to the fact that lighter elements such as carbon and oxygen cannot be accurately quantified by this EDS system . However, there appeared to be a fairly large amount of oxygen indicating the presence of metal oxides, likely chromium oxide.…”
Section: Resultsmentioning
confidence: 92%
“…The majority of particles appear to be chromium oxide, but alloy particles, chromium phosphate, and metallo-organic complexes have also been reported. 46 Our group has previously established the differential response by the processed and unprocessed states of degradation products obtained from hip simulator in inducing neurodegeneration 47 . Hence, it is imperative to study the differentiation of macrophages in response to the clinically relevant wear particles to improve our understanding of macrophage action at the taper interface.…”
Section: Macrophage Polarization By Nanomaterialsmentioning
confidence: 99%
“…The original stock solution was stored at −20°C and an aliquot of stock was refrigerated at 4°C (0-4 months) until use. The endotoxin levels of the particle samples were checked prior to cell culture tests 47 .…”
Section: Wear Particles Generationmentioning
confidence: 99%
See 1 more Smart Citation